A Review on Novel Analytical Method Development and Validation by RP-HPLC Method - Suyash Gupta; Preeti Verma; Abhinav Prasoon Mishra; Nainshi Omar; Riya Mathur (Indian Journal of Forensic Medicine & Toxicology, 2021)
A simple, precise, accurate, specific and RP-HPLC method was developed for determination of drug inpharmaceutical formulation. Analytical method development and validation play important roles in thedrug discovery, drug development and manufacture of pharmaceuticals. It involves detection of the purityand toxicity of a drug substance. The present study focuses on the various steps, parameters involved inHPLC condition. It can be adopted apparently for routine quality control study of research and formulationtests. This article mainly focuses on the optimization of HPLC conditions and other important aspectsduring method of process development and validation of drug substances. The main objective of this reviewis to elaborate the novel analytical techniques utilized in method development and validation of variedpharmaceuticals because it is extremely much significant for the steadiness, efficacy and quality of thedrug product. Various validation parameters like accuracy, specificity, precision, linearity, LOD, LOQ,ruggedness, and robustness also are listed concerning ICH Guidelines. Validation is extremely much usefulfor the standard control and quality assurance of pharmaceuticals and therefore the safety of patients.